2016
DOI: 10.1158/1538-7445.am2016-4716
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4716: Dimethyl fumarate impairs breast cancer growth and inhibits the nuclear factor κB pathway in breast cancer cells by covalent modification of p65

Abstract: Despite major advances in breast cancer treatment, successful therapy outcome is limited to early detection of cancer at the primary organ. Therapy options for aggressive, advanced stage, metastatic and recurring cancers are limited and this translates to poor patient outcome contributing to over 40,000 deaths each year in the United States. A key underlying factor of aggressive breast cancers is activation of the inflammatory nuclear factor κB (NFκB) pathway because it promotes numerous phenotypes such as cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…DMF has been demonstrated promising in the treatment of psoriasis and multiple sclerosis treatment [21][22][23]. A review of the literature indicated that DMF exerts multiple pharmacological effects, including anti-in ammatory [24,25], immunomodulatory [26,27] and antineoplastic effects [28][29][30][31] in different cell types. Despite these promising results, the mechanisms underlying the anticancer action of dimethyl fumarate are not fully understood, and the cellular targets of DMF in HCC cells remain unidenti ed.…”
Section: Discussionmentioning
confidence: 99%
“…DMF has been demonstrated promising in the treatment of psoriasis and multiple sclerosis treatment [21][22][23]. A review of the literature indicated that DMF exerts multiple pharmacological effects, including anti-in ammatory [24,25], immunomodulatory [26,27] and antineoplastic effects [28][29][30][31] in different cell types. Despite these promising results, the mechanisms underlying the anticancer action of dimethyl fumarate are not fully understood, and the cellular targets of DMF in HCC cells remain unidenti ed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of molecular or immunological factors have been investigated to explore their potency to sensitize breast cancer cells [24][25][26][27] alongside other cancers [28,29] for therapeutic agents. Many researchers indicated the ability of DMF to inhibit NF-κB in many types of cancers and tumors [30,31]. The current work aims to explore the combination of PDT and DMF for NF-kB inhibition as a novel strategy against triple negative breast cancer, as both treatments are already clinically approved therapies in human patients.…”
Section: Introductionmentioning
confidence: 99%